Green cosmetics and Gen Z in Kudus, Indonesia: What drives eco-friendly purchases in a small city?‎ - Noor, Sufiana; Marka, Mira Meilia; Bintang, Yasmin Mutiara (Universitas Islam Indonesia, 2025)
IntroductionThe Indonesian cosmetics industry is rapidly expanding, yet it raises environmental concerns, particularly from packaging waste. Generation Z, known for its environmental consciousness, emerges as a critical market segment for eco-friendly cosmetics. However, consumer purchase intentions toward these products remain inconsistent across studies, especially in smaller, culturally distinct regions such as Kudus.ObjectivesThis study aims to investigate the influence of green marketing, green brand image, and green perceived quality on purchase intention of eco-friendly cosmetics among Generation Z in Kudus. It also examines the mediating role of green trust in strengthening these relationships.MethodA quantitative research approach was used with an associative causal design. Data were collected via an online questionnaire from 105 respondents aged 13–28 years in Kudus who had experience using eco-friendly cosmetics. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software.ResultsThe results reveal that green brand image, green perceived quality, and green trust significantly influence purchase intention. Green marketing showed no direct effect but had an indirect influence through green trust. The adjusted R² value for purchase intention was 0.465, indicating that the model explains 46.5% of the variance. Generation Z in Kudus values product authenticity, ethical branding, and halal-certification as critical to building trust and influencing behavior.ImplicationsThe findings highlight that marketers must focus on building green trust by ensuring product transparency, environmental commitment, and culturally relevant messaging. Green brand image and product quality are key drivers in developing consumer trust and encouraging sustainable buying behavior among Gen Z.Originality/NoveltyThis research enriches the Theory of Planned Behavior by incorporating green trust as a mediating factor and applying it within a unique socio-religious Gen Z demographic in a small Indonesian city. It provides novel insights into how eco-conscious values interact with trust and marketing in shaping local green consumption patterns.